Regional and genus-specific factors underpin bleaching variation across India’s corals reefs during the fourth global coral bleaching event - Wenzel Pinto; Karan Deshpande; Aaron Savio Lobo; Abhishek Jamalabad; Afreen Hussain; Anish Paul; Arpita Dutta; Chaitanya Arjunwadkar; Farai Divan Patel; Harshul Thareja; Ishan Nangia; Jeremy Josh; et al. (Coral Reefs, 2026)

An Extended-Release Injectable Suspension of Meloxicam for Pain Management in Veterinary Applications - Sruthi Turaga; Daniel Yong; Guru Raghavendra Valicherla; Steven Leary; Susan Witham; Barry Levinson; Lisa Rohan; Sravan Kumar Patel (Journal of Pharmaceutical Innovation, 2026)

Application of a Liquid Chromatography: Tandem Mass Spectrometry Based Method to Determine Plasma Cycloserine Concentrations in Indian MDR-TB Patients—A Pilot Study - Rohan V. Lokhande; Prerna R. Arora; Camilla Rodrigues; Ganesh R. Bhagure; Zarir F. Udwadia; Amita Gupta; Jeffrey A. Tornheim; Tester F. Ashavaid; Lancelot M. Pinto; Jai B. Mullerpattan; Ayesha Sunavala; Jigneshkumar Patel; et al. (Indian Journal of Clinical Biochemistry, 2026)

Biomass-derived N-doped carbon to anchor bimetallic-phospho boride for hydrogen evolution from alkaline seawater - R. Silviya; Suraj Gupta; Matjaž Spreitzer; Nainesh Patel; Rohan Fernandes (Fuel, 2026)

Instigating the mixed phases of cobalt oxide in nanowires for electrolysis of urea-based water - Aniruddha Bhide; Suraj Gupta; Rinkoo Bhabal; Rohan Fernandes; Maulik Patel; Nainesh Patel (Fuel, 2026)

Furamidine enhances IL-23-mediated autophagic response through IL-23R-TYK2-STAT3-dependent regulation of intracellular Ca²⁺ level to facilitate mycobacterial clearance in human macrophages - Salina Patel; Mousumi Das; Dev Kiran Nayak; Pramathesh Kumar Dandsena; Mustafeez Ali Quaderi; Amit Mishra; Surajit Das; Ramandeep Singh; Lincoln Naik; Rohan Dhiman (Medical Microbiology and Immunology, 2025)

Immunomodulatory activity of 4-(Benzyloxy)phenol facilitates intracellular mycobacterial clearance through p53 mediated IL-35 signaling dependent JAK1/STAT3 pathway in human macrophages - Lincoln Naik; Salina Patel; Mousumi Das; Dev Kiran Nayak; Pramathesh Kumar Dandsena; Mustafeez Ali Quaderi; Ashish Kumar; Amit Mishra; Ramandeep Singh; Abtar Mishra; Rohan Dhiman (Immunologic Research, 2025)

Assessment of the Vulnerability of Land and Water Resources at the Sub-Basin Scale of One of the Sensitive Catchments of the Mahanadi River Basin, India - Rohan Kar; Pooja Patel (Environmental Modeling & Assessment, 2025)

Surface modified Cobalt Oxide Nanostructures for hydrogen generation from catalytic dissociation of NaBH4 - Anitha Abraham; Suraj Gupta; Rupali Patel; Nainesh Patel; Rohan Fernandes (Fuel, 2025)

Diversity of secondary metabolites from marine Streptomyces with potential anti-tubercular activity: a review - Salina Patel; Lincoln Naik; Ankita Rai; Krishna Palit; Ashish Kumar; Mousumi Das; Dev Kiran Nayak; Pramathesh Kumar Dandsena; Amit Mishra; Ramandeep Singh; Rohan Dhiman; Surajit Das (Archives of Microbiology, 2025)

Dual strategy for enhanced photocatalytic degradation of tetracycline: Phosphorus doping and cobalt boride co-catalyst loading on g-C3N4 - M. Vinay Kumar; Murilo Fendrich; Michele Orlandi; Antonio Miotello; Suraj Gupta; Rupali Patel; Rohan Fernandes; Nainesh Patel (Journal of Water Process Engineering, 2025)

Integration of Biochar with Chemical Fertilizers Improves the Economic Yield, Quality of Holy Basil (Ocimum sanctum L.) and Soil Health - Praveen Singh; B. B. Basak; V. J. Patel; Rohan Sarkar; K. C. Patel; G. N. Motaka (Journal of Soil Science and Plant Nutrition, 2024)

Fused Deposition Modeling-Based 3D Printing as a Versatile Technology to Manufacture Vaginal Films Incorporating Metronidazole - Zhongfang Zhang; Elaine Xu; Ronald Max Puntil; Nicholas Youwakim; Christina Bagia; Lisa C. Rohan; Sravan Kumar Patel (Journal of Pharmaceutical Innovation, 2024)

Modelling the influence of road elevation on pollutant dispersion - James O’Neill; Martin Seaton; Kate Johnson; Jenny Stocker; Rohan Patel; Martine Van Poppel; David Carruthers (Air Quality, Atmosphere & Health, 2024)

Exploring Sorafenib and Simvastatin Combination for Ferroptosis-Induced Cancer Treatment: Cytotoxicity Screening, In Vivo Efficacy, and Safety Assessment - Kaushik Kuche; Vivek Yadav; Meet Patel; Rohan Ghadi; Sanyog Jain (AAPS PharmSciTech, 2023)

Carbonate budgets in Lakshadweep Archipelago bear the signature of local impacts and global climate disturbances - Farai Divan Patel; Wenzel Pinto; Mayukh Dey; Teresa Alcoverro; Rohan Arthur (Coral Reefs, 2023)
Predicted sea-level rise and increased storm frequency caused by climate change drastically threaten low-lying inhabited coral atolls. Coral reef frameworks are the atolls’ primary defence from these changes. The growth and integrity of these frameworks is reflected in their carbonate budgets, a dynamic balance between biogenic accretion through coral growth and erosional forces, both of which are affected by factors acting at different spatial scales. We explored how carbonate budgets, estimated using the ReefBudget methodology, vary between three inhabited atolls that face differing anthropogenic stressors in the Lakshadweep Archipelago in the Northern Indian Ocean. We surveyed ten reefs, at two depths each, across the three islands. Overall, net carbonate budgets of reefs across all atolls were below optimal production rates needed to continue protecting shorelines (5 G measured on healthy reefs). This was a result of repeated mass bleaching events as well as local impacts. Carbonate production was influenced by a recent mass bleaching event in 2016 and a cyclone in 2018, and varied between depths and exposures, potentially due to differential recovery and mortality dynamics. Erosional processes were locally mediated with both urchin and parrotfish density showing large differences between islands, possibly linked to nutrient outflow and fishing intensity. We also find that by the year 2100, a large proportion of shallow sites will experience an increase in water depth above half a metre under moderate and high emissions scenarios, but none will breach this threshold under a low emissions scenario. Our results show that patterns of carbonate production were largely mediated by the history of global/regional disturbances, while erosional rates were much more dependent on local factors.

Groundwater arsenic contamination: impacts on human health and agriculture, ex situ treatment techniques and alleviation - Bhavi Patel; Rohan Gundaliya; Bhavya Desai; Manan Shah; Jainish Shingala; Daya Kaul; Anurag Kandya (Environmental Geochemistry and Health, 2023)

Development of a novel method for multiple phytohormone analysis by UHPLC-MS/MS from bio-enriched organic fertilizer prepared using banana pseudostem sap waste - Harihar Vaidya; Vanrajsinh H. Solanki; Rohan V. Kansara; Chirag Desai; Susheel Singh; Jayesh Patel; Trupti K. Vyas; Hiren Patel (Environmental Science and Pollution Research, 2022)

A comprehensive and systematic study of fluoride and arsenic contamination and its impacts in India - Het Baboo; Takshil Patel; Rohan Faldu; Manan Shah; Harshad Shah (Sustainable Water Resources Management, 2022)

In vitro regeneration through indirect organogenesis, genetic uniformity analysis and mineral content determination of finger millet (Eleusine coracana L.) - Rohan V. Kansara; Vanrajsinh H. Solanki; Vishal S. Srivashtav; Ramesh M. Patel; Kelvin D. Gandhi; Vivek S. Mehta (Biologia, 2022)

CYP2C19 Loss-of-Function Associated with First-Time Ischemic Stroke in Non-surgical Asymptomatic Carotid Artery Stenosis During Clopidogrel Therapy - Pious D. Patel; Xinnan Niu; Chevis N. Shannon; Joshua C. Denny; Josh F. Peterson; Matthew R. Fusco; Rohan V. Chitale (Translational Stroke Research, 2022)

Co-delivery of cisplatin and siRNA through hybrid nanocarrier platform for masking resistance to chemotherapy in lung cancer - Vivek Patel; Rohan Lalani; Imran Vhora; Denish Bardoliwala; Akanksha Patel; Saikat Ghosh; Ambikanandan Misra (Drug Delivery and Translational Research, 2021)

Updated Analysis of the Oncology Section of the OITE from 2007 to 2019 - Tyler Hoskins; David Goyette; Jay N. Patel; Filippo Romanelli; Christopher Mazzei; Laura Sonnylal; Rohan Sampat; James C. Wittig (Journal of Cancer Education, 2021)

Nanocrystal Formulation Improves Vaginal Delivery of CSIC for HIV Prevention - Tiantian Gong; Sravan Kumar Patel; Michael A. Parniak; Byron Ballou; Lisa C. Rohan (AAPS PharmSciTech, 2019)

Novel Application of Hot Melt Extrusion for the Manufacturing of Vaginal Films Containing Microbicide Candidate Dapivirine - Galit Regev; Sravan Kumar Patel; Bernard J. Moncla; John Twist; Brid Devlin; Lisa C. Rohan (AAPS PharmSciTech, 2019)

Lipid-Based Oral Formulation Strategies for Lipophilic Drugs - Vivek Patel; Rohan Lalani; Denish Bardoliwala; Saikat Ghosh; Ambikanandan Misra (AAPS PharmSciTech, 2018)

Colloidally Stable Small Unilamellar Stearyl Amine Lipoplexes for Effective BMP-9 Gene Delivery to Stem Cells for Osteogenic Differentiation - Imran Vhora; Rohan Lalani; Priyanka Bhatt; Sushilkumar Patil; Hinal Patel; Vivek Patel; Ambikanandan Misra (AAPS PharmSciTech, 2018)

On-demand microbicide products: design matters - Sravan Kumar Patel; Lisa Cencia Rohan (Drug Delivery and Translational Research, 2017)

Cell-Instructive Graphene-Containing Nanocomposites Induce Multinucleated Myotube Formation - Akhil Patel; Yingfei Xue; Shilpaa Mukundan; Lisa C. Rohan; Vinayak Sant; Donna B. Stolz; Shilpa Sant (Annals of Biomedical Engineering, 2016)

A Systematic Review of Male Gender, History of Prior Injury, Full Time Working Status and Farm Owner/Operator Status as Risk Factors for Agricultural Injuries - Rohan Jadhav; Lina Lander; Chandran Achutan; Gleb Haynatzki; Shireen Rajaram; Ketki Patel; Risto Rautiainen (Journal of Agromedicine, 2014)